Enhanced Immobilization of Cr(VI) in Soils by the Amendment of Rice Straw Char. Issue 5 (3rd July 2016) - Lee, Chun-Chi; Huang, Jang-Hung; Lin, Liang-Ying; Wang, Shan-Li
ABSTRACT: This study investigated the effect of rice straw char (RSC) on the immobilization of Cr(VI) in soils. The Cr(VI) sorption experiments on the RSC and RSC-amended soils were conducted using the batch method. RSC exhibited Cr(VI) reduction capacity due to its black carbon content. The addition of RSC to the soils enhanced the overall Cr(VI) immobilization of the soils, which is primarily attributed to the Cr(VI) reduction capacity of RSC. The effects of RSC amendment on the Cr(VI) sorption of the soils increased with increasing RSC content in the soils and decreased with increasing pH or anion contents in the soil solutions. After Cr(VI) was sorbed by the soils, a portion of the Cr(VI) was converted to Cr(III) and the remainder was sorbed onto the soils. The presence of RSC in the soils decreased the portion of sorbed Cr(VI) in the soils and therefore lowered the potential remobilization of Cr(VI) from the soils. The results suggested that RSC amendment can be applied to develop a cost-effective method for immobilizing Cr(VI) in polluted soils, thus lowering the environmental risk from Cr(VI) toxicity.